Outcomes of penetrating keratoplasty in congenital hereditary endothelial dystrophy. Issue 1 (6th May 2017) - AlArrayedh, Hamed; Collum, Louis; Murphy, Conor C
Abstract : Background/aim: To report the outcome of penetrating keratoplasty (PKP) in Irish patients with congenital hereditary endothelial dystrophy (CHED). Methods: A retrospective case series review of patients with CHED who underwent PKP was conducted. The outcomes of PKP in 14 patients with CHED at the Royal Victoria Eye and Ear Hospital in Dublin from 1978 to 2013 were described following case note review. The main outcome measures were best-corrected visual acuity (BCVA) and graft survival. Results: Thirty-three corneal transplants were performed, which included 32 PKPs and one Descemet's stripping endothelial keratoplasty. Twenty-four eyes underwent primary corneal grafts and nine eyes had regrafts. The graft survival rates at final follow-up were 37.5% and 33% in the primary graft and regraft groups, respectively. Preoperative BCVA was 20/200 or worse in all patients. At the final postoperative visit, the BCVA was 20/80 or better in four eyes following primary PKP, 20/160 in one eye following regrafting and was 20/200 or worse in all other eyes. The mean time to graft failure was 16 months (range 0–37 months). The mean follow-up time was 101 months (range 12–252 months). Fifty per cent of the patients continue to attend for follow-up. Conclusions: This study has demonstrated a poor outcome from PKP for CHED in this Irish cohort. This arises from a combination of dense amblyopia and a high risk of graft failure in the long term.